Radiographic assessment of keratocyst odontogenic tumor in maxilla using cbct: a case report - Pramatika, Berty (JITEKGI Jurnal Ilmiah dan Teknologi Kedokteran Gigi, 2018)
Keratocyst odontogenic tumor (KCOT) is a developmental odontogenic cyst of epithelial origin. This lesion shows features of a cyst and a benign neoplasm, because of its behavior, autonomous growth, and potential for recurrence. The KCOT occurs more significant in the posterior mandible than in maxilla. Occasionally, pain, swelling, and drainage indicate a secondary infection of the cyst. Asymptomatic KCOT usually detected in routine radiograph.  The radiographic examination is important to determine KCOT diagnose and treatment planning to prevent recurrence. The aim of this case report is to describe radiographic characteristic of keratocyst odontogenic tumor in maxilla using CBCT. A 20 year-old women patient was referred to the oral maxillofacial radiology department of Padjadjaran University with the  chief complaint of swelling, painless in the anterior of the upper jaw. In this presented case, we used cone beam computed tomography to find out the margin of the cortical extension, and diameter of the lesion. The CBCT examination shows radiolucent, well-defined lesion in 12-14 region with displacement of 12. The size of the lesion is about 20x15x19mm extended posterior-superiorly near to nasal cavity and it shows less degree of bone expansion. Based on radiographic and clinical examination, the diagnosis was keratocyst odontogenic tumor. KCOT has some radiographic characteristic distinguishable with another odontogenic lesion. Therefore; cbct examination is recommended for the diagnosis of odontogenic keratocysts and proper surgical planning.